Insight into molecular dynamics simulation of BRAF(V600E) and potent novel inhibitors for malignant melanoma - Tang HC (Dove Medical Press, 2015)
Hsin-Chieh Tang,1 Yu-Chian Chen1–3 1Department of Biomedical Informatics, Asia University, Taichung, Taiwan; 2Human Genetic Center, Department of Medical Research, 3Research Center for Chinese Medicine and Acupuncture, China Medical University Hospital, Taichung, Taiwan Abstract: BRAF inhibitors have changed the standard therapeutic protocol for advanced or metastatic melanoma which harbored notorious BRAF(V600E) single mutation. However, drug resistance to BRAF inhibitors happens just like other cancer treatment. In this study, we constructed the ideal BRAF(V600E)-modeled structure through homology modeling and introduced the method of structure-based docking or virtual screening from the large compound database. Through certain methods of molecular dynamics simulation, we realized that BRAF(V600E) had quite prominent difference of molecular character or structural variation from the wild-type BRAF protein. It might confer the metamorphic character of advanced melanoma for the patients who harbored BRAF(V600E) mutation. By the methods of ligand-based quantitative structure-activity relationship and molecular dynamics simulation, we further recommend that aknadicine and 16beta-hydroxy-19s-vindolinine N-oxide from the traditional Chinese medicine are potent novel inhibitors for the management of malignant melanoma in the future. Keywords: BRAF inhibitor, structure-based, virtual screening, docking, ligand-based, quantitative structure-activity relationship (QSAR)